Pengaruh Disiplin Kerja, Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Perangkat Desa di Wilayah Kecamatan Wirosari Kabupaten Grobogan - Ica Aprilianti; Sudarmadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze the extent to which work discipline, leadership style, and work motivation influence the performance of village officials in Wirosari Subdistrict, Grobogan Regency. The study involved 82 respondents using a saturated sampling method. The results of data analysis indicate that work discipline, leadership style, and work motivation each have a positive and significant impact on performance. Furthermore, when assessed collectively, these three factors also demonstrate a significant positive effect on their performance. Overall, leadership style, work discipline, and motivation contribute 59.7% to the variation in the performance of village officials, providing valuable insights for improving performance.